(untitled) - Cheremisinoff, Nicholas P . (Amsterdam, The Netherlands, 2003)
Source reduction and waste minimization. Environmental laws and regulatory drivers. Municipal solid waste. Landfill operations and gas enery recovery.
Quản lý và tận dụng phụ phẩm trong sản xuất thực phẩm
Keywords: Refuse refuse dispossal,Waste minimaization